KAJIAN EROSI TANAH AKIBAT ALIH GUNA LAHAN DI DAS OLONJONGE KABUPATEN PARIGI MOUTONG SULAWESI TENGAH - Harijanto, Herman (ForestSains, 2017)
This research was conducted in the Olonjonge watershedÂ  Parigi Moutong with purpose (i) to determine the level of erosion that occurs in various forms of land use in the watershed area Olonjonge, Central Sulawesi, (ii) to study the relationship between the elements of rain with soil erosion.This study used a survey method. Measurement of the amount of erosion using plou measuring erosion (PUE) were placed on each of the forms of land use (land of cocoa monoculture, fields, gardens and forest mix). To study the relationship between rainfall and soil erosion, rainfall and surface runoff and surface runoff and soil erosion used simple linear regression analysis.The results showed that the rate of soil erosion found in most field area of 0.50 tonnes / ha / yr, followed by the brown area monoculture 0.23 tonnes / ha / yr, mixed garden 0.14 tonnes / ha / yr and forest areas, 0 , 07 tonnes / ha / yr) Relationship between rainfall rate and soil eroded indicate a trend that increased rainfall will result in increased mass of eroded soil.This research was conducted in the Olonjonge watershedÂ  Parigi Moutong with purpose (i) to determine the level of erosion that occurs in various forms of land use in the watershed area Olonjonge, Central Sulawesi, (ii) to study the relationship between the elements of rain with soil erosion.This study used a survey method. Measurement of the amount of erosion using plou measuring erosion (PUE) were placed on each of the forms of land use (land of cocoa monoculture, fields, gardens and forest mix). To study the relationship between rainfall and soil erosion, rainfall and surface runoff and surface runoff and soil erosion used simple linear regression analysis.The results showed that the rate of soil erosion found in most field area of 0.50 tonnes / ha / yr, followed by the brown area monoculture 0.23 tonnes / ha / yr, mixed garden 0.14 tonnes / ha / yr and forest areas, 0 , 07 tonnes / ha / yr) Relationship between rainfall rate and soil eroded indicate a trend that increased rainfall will result in increased mass of eroded soil.